Cu/Ag‐Cocatalyzed Aerobic Oxidative Amination and CuCl2‐Mediated Aerobic Oxidative Chloroamination of Maleimides. Issue 32 (18th October 2016) - An, Yu‐Long; Zhang, He‐Hui; Yang, Zhen‐Hua; Lin, Long; Zhao, Sheng‐Yin
Abstract : An efficient Cu(OAc)2 /Ag2 CO3 ‐cocatalyzed approach for the synthesis of 3‐aminomaleimides and 3‐amino‐4‐indolylmaleimides has been developed with satisfactory yields. A series of primary and secondary amines are compatible with this reaction. In addition, treatment of maleimides with primary amines using 1 equiv. of CuCl2 leads to the formation of chloroamination products such as 3‐amino‐4‐chloromaleimides by a radical‐type mechanism. Abstract : A new aerobic oxidative amination of maleimides catalyzed by Cu/Ag cocatalysts, and an aerobic oxidative chloroamination of maleimides mediated by CuCl2 have been developed. A series of 3‐aminomaleimides, 3‐amino‐4‐indolylmaleimides, and 3‐amino‐4‐chloromaleimides have been synthesized in satisfactory yields.